KAJIAN BANGUNAN VIHĀRA SUKJAI SAILENDRA BERDASARKAN KAIDAH ARSITEKTUR HEMAT ENERGI DENGAN TOLAK UKUR KENYAMANAN TERMAL - Tiurma Leonora Ritonga, Isniar; Martha Mulia, Endi; Costa, Luis; Shan Lee, Belinda (Jurnal Sains dan Teknologi ISTP, 2025)
This research aims to examine the Vihāra Sukjai Sailendra building based on energy-saving architectural principles using temperature, humidity, and wind speed as benchmarks. The method used in this research is a qualitative method with a case study approach through observation.. The results of this research show that the Vihāra Sukjai Sailendra building is not an energy-efficient building when measured in terms of temperature. However, if measured in terms of humidity and wind speed, the Vihāra Sukjai Sailendra building is an energy-efficient building because it utilizes natural ventilation through multiple wall openings that create cross-ventilation, allowing the indoor air conditions to remain comfortable without the need for artificial cooling systems that require electrical energy to operate.